Disclosure of organizational information on social media: Perspectives from security managers - Abdul Molok , Nurul Nuha; Chang, Shanton; Ahmad, Atif (2013)
Despite the benefits of social media to organizations, the pervasive online social networking (OSN) among employees has been reported to be detrimental to organizations. The ubiquity of social technologies makes employees’ professional and personal boundaries unclear, allowing inadvertent leakage of organizational information through the public domain. Without proper information security management, social media could be a double-edged sword to organizations. Hence, some organizations are employing various security strategies to mitigate employees’ use of these social platforms. While cases of information leakage through OSN have been reported worldwide, its coverage in academic literature is scant. This paper aims to fill in this research gap. It reports the findings of a qualitative multiple-case study to unravel information security issues that OSN might bring to organizations. It also describes the security strategies employed by organizations and factors that influenced the strategy decision. The understanding of this contemporary phenomenon and organizational security strategy contributes to the development of a theoretical framework that may offer practical insight to organizations.